Vous êtes sur la page 1sur 20

 OX OY V V OX OY = (x o , y o ) = (x o , y o ) B = 0 AC = 0

a

b x

y

y

a

x = x

y =

b

b = 2a y x 3 = 2a 3 x 2 = ay, y 2 = 2ax xy = 2a 2

Ax 2 + Cy 2 + Dx + Ey + F = 0

A C

 L F L P F L F L P = { P | d(P, F ) = d(P, L) } .

F

L P

P

V P

P

A L V AF

2p = d(F, L) P d(V, F ) = d(V, L) = p

F L

L
/
/
A
V
F

P F V L P ∈ P P P P P Q P P P QF P QF d(P, F ) = d(P , F)

L
B P
A V
Q F
B
P

P

d(P, L) = d(Q, L) = d(P , L) BP QA AQP B P ∈ P d(P, F ) = d(P, L) d(P , F) = d(P , L) P ∈ P

OXY

OX

F L

P V = (0, 0) F = (p, 0) L : x = p 2p = d(F, L)

P = (x, y) ∈ P

Y
L
P
(p, 0)
(−p, 0)
V
F X

P : y 2 = 4px

⇐⇒

⇐⇒

⇐⇒

⇐⇒

⇐⇒

⇐⇒

d(P, F ) = d(P, L)

(x p) 2 + y 2 = |x + p|

(x p) 2 + y 2 = (x + p) 2

x 2 2px + p 2 + y 2 = x 2 + 2px + p 2

2px + y 2 = 2px

y 2 = 4px

F L

F

= (p, 0) L : x = p 2p = d(F, L)

P = (x, y) ∈ P

 ⇐⇒ d(P, F ) = d(P, L) ⇐⇒ (x + p) 2 + y 2 = |x − p| ⇐⇒ (x + p) 2 + y 2 = (x − p) 2 ⇐⇒ x 2 + 2px + p 2 + y 2 = x 2 − 2px + p 2 ⇐⇒ 2px + y 2 = −2px ⇐⇒ y 2 = −4px
Y L
P
(p, 0)
(−p, 0)
V
F
X

P : y 2 = 4px

OY

F L

F

= (0, p) L : y = p 2p = d(F, L)

P = (x, y) ∈ P

⇐⇒ x 2 + (y p) 2 = |y + p| ⇐⇒

x 2 = 4py

Y
F
(p, 0)
P
V
X
L
(−p, 0)

P : x 2 = 4py

Y
(p, 0)
L
V
P X
F
(−p, 0)

P : x 2 = 4py

F L

F

= (0, p) L : y

=

p

2p = d(F, L)

(x, y) ∈ P

x 2 + (y + p) 2 = |y p| ⇐⇒

x 2 = 4py

P

=

P V

F = (3, 0)

L : x = 3

P

F = (0, 2) p = d(V, F ) = 2 = OY F L : y = 2 P : x 2 = 8y

F

p = d(V, F ) = 3

: y 2 = 12x

= OX

P (4, 2) V OY F L

P : x 2 = ±4py

p = d(V, F ) > 0

P

P

p = 2 F = (0, 2) L : y = 2 P :

x 2 = 8y

(4, 2)

: x 2

= 4py

16 =

8p

Y
L : y=2
2
4
V
X
P
−2
F
(4,−2)

P : x 2 = 8y

P : x 2 = 16y L C

P OY

F

4p = 16

C

C

=

(4, 1)

F

= (0, 4) L : y = 4

C : (x 4) 2 + (y + 1) 2 = r 2

F

= (0, 4) ∈ C 16 + 9 = r 2 r = 5

( x, y ) ∈ C ∩ L ⇐⇒ ( x 4) 2 + (4 + 1) 2 = 5 2 ⇐⇒ (x 4) 2 = 0 ⇐⇒ x = 4 ⇐⇒ (x, y) = (4, 4) L C (4, 4)

Y
L : y=4
4
V
4
X
(4,−1)
−1
P
−4
F
C

P C L

V = (x o , y o ) OX

P V = (x o , y o ) OX

O X Y O = V = (x o , y o ) O X O Y OX OY

F L

O X Y

P

:

y 2

= 4px

F

(p, 0)

V

=

=

(0, 0)

L : x = p : y = 0

x = x + x o

y = y + y o

P

P : (y y o ) 2 = 4p(x x o )

F = (x o + p, y o )

 • V = (x o , y o ) • L : x − x o = −p
Y
L
Y
P
y+y o
y
P
V
x
F
y
o
O
X
x
O
o
X
x o −p
x+x o
x o +p

L : x = x o p

: y y o = 0 : y = y o

P : (y y o ) 2 = 4p(x x o )

F L

O X Y

y 2 = 4px

: y = 0

: x = p

x y OXY

F

= (p, 0) V

= (0, 0)

L

P : (y y o ) 2 = 4p(x x o )

F = (x o p, y o )

L : x x o = p

L : x = x o + p

: y = y o

V = (x o , y o )

:

y y o

=

0

Y
P
Y
L
P
y+y o
y
x
V
F
y
o
O
X
x
O
o
X
x o −p
x+x o
x o +p

P :

(y y o ) 2 = 4p(x x o )

V = (x o , y o ) OY

O X Y

OX OY

V OY

O = V

= (x o , y o )

O X

O Y

= (x o , y o )

F L
F
= (x o , y o + p)
L : y
= y o − p
: x = x o
(x − x o ) 2 = 4p(y − y o )
Y
Y
Y
Y
P
y o +p
y o +p
F
L
y
y+y o
P
V
y
o
V
x
y
o
x
O
X
O
X
P
y+y o
y
y o −p
L
F
y o −p
P
x
O
o
x+x o
x
X
O
o
x+x o
X
P
: (x − x o ) 2 = 4p(y − y o )
P : (x − x o ) 2 = −4p(y − y o )
F L
F
= (x o , y o − p)
L : y
= y o + p
: x = x o
(x − x o ) 2 = −4p(y − y o )

P V = (3, 4) F = (3, 2)

 V = (3, 4) F = (3, 2) : x = 3

F V L P : (x 3) 2 = 4p(y 4)

 p d(V, F ) = 2 = L : y = 6

P : (x 3) 2 = 8(y 4)

Y
L:y=6
6
V
4
2
F
P
O
3
X
:x=3

P : (x 3) 2 = 8(y 4)

B = 0 AC = 0

P OX 3 , 1 (0, 5) (6, 7)

P OX P : (y y o ) 2 = ±4p(x x o )

2

P : y 2 + Dx + Ey + F = 0 .

 3 D − E + F = −1 2 5E + F = −25 −6D − 7E + F = −49 .

D = 8 E = 2 F = 15

y 2 + 8x 2y 15 = 0

y 2 2y + 1 = 15 8x + 1

P

4p

OX

P : (y 1) 2 = 8(x 2)

V

=

8

p

= (2, 1) : y = 1

=

2

F

F

= (0, 1) L : x = 4 P

B = 0 AC = 0

V = (x o , y o ) OX (y y o ) 2 = ±4p(x x o ) .

y 2 4px 2y o y + y

2

o

± 4px o = 0 .

Ax 2 + Bxy + Cy 2 + Dx + Ey + F = 0 A = 0 B = 0 C = 1 D = 4p E = 2y o F = y

2

o

± 4px o

V = (x o , y o ) OY (x x o ) 2 = ±4p(y y o ) ,

x 2 2x o x 4py + x o

2

± 4py o = 0

Ax 2 + Bxy + Cy 2 + Dx + Ey + F = 0

2

A = 1 B = 0 C = 0 D = 2x o E = 4p F = x o ± 4py o

A = 0 B

= 0 C

= 0

B = 0 C = 0

B = 0 AC = 0

A

= 0

 B = 0 Ax 2 + Cy 2 + Dx + Ey + F = 0. A = 0 C = 0 • OX D = 0 • OX D = 0 E 2 − 4CF > 0 • OX D = 0 E 2 − 4CF = 0 • D = 0 E 2 − 4CF < 0 C OX OY = 0 A = 0

A = 0 C

= 0 D

= 0

y 2 + E y + D x + F

C

C

C

= 0.

y +

E

2C 2 + D

C

x + C F

E

2

4C 2 = 0 .

D

= 0

y +

2C 2 = D

E

C

x +

C

D

F

C

E 2

4C

2 ,

B = 0 AC = 0

OX

V

= 4C 2 F CE 2 4C 2 D

,

2C .

E

D = 0 Cy 2 + Ey + F = 0

OX

y = E + E 2 4CF

2C

E 2 4CF > 0

OX y = E

2C

E 2 4CF

E 2 4CF < 0

= 0

y = E E 2 4CF

2C

Ax 2 +Cy 2 +Dx+Ey+F = 0 AC = 0

x 2 8y = 0

x 2 = 8y

V = (0, 0)

= OY

2p = 4 (=p = 2)

F = (0, 2)

2y 2 + 5x + 8y 7 = 0

: x = 0

L : y = 2

 2(y 2 + 4y) = −5x + 7 ⇐⇒ 2(y 2 + 4y + 4) = −5x + 7 + 8 ⇐⇒ 2(y + 2) 2 = −5x + 15 ⇐⇒ 2(y + 2) 2 = −5(x − 3) ⇐⇒ (y + 2) 2 = − 5 2 (x − 3) ,

 • V = (3, −2) • : y = −2 OX • 2p = 5 4 (=⇒ p = 5 8 ) • F = 3 − 5 8 , −2 = 19 , −2 8 • L : x = 3 + 8 5 = 29 8 3y 2 + 7y − 6 = 0 A = B = D = 0 49 + 4 × 3 × 6 = 121 > 0 y = −7 ± 11 6 y = −3 y = 2 3 OX 9x 2 + 42x + 49 = 0 B = C = E = 0 42 2 − 4 × 9 × 49 = 1764 − 1764 = 0 x = − 42 18 = − 21 OY 9 3y 2 − 2y + 1 = 0 = − 7 3 A = B = D = 0 4 − 12 = −8 < 0 V = (−2, −1) P L : x + 2y = 1

(1, 2) ⊥ L (2, 1) : 2xy = 4+1 = 3 A = (x, y) L x y

2x y

x + 2y = 1

= 3

2x y

= 3

2x 4y = 2 .

5y = 5 y = 1 x = 1 2y = 1

 V AF F = 2V − A F = 2(−2, −1) − (−1, 1) = (−3, −3) P = (x, y) ∈ P d(P, F ) = d(P, L)

B = 0 AC = 0

⇐⇒

⇐⇒

(x + 3) 2 + (y + 3) 2 2 =

|x + 2y 1|

5

2

= (x + 2y 1) 2

(x + 3) 2 + (y + 3) 2

x 2 + 6x + 9 + y 2 + 6y + 9 =

5 x 2 + 4xy + 4y 2 2x 4y + 1

5

 ⇐⇒ 5x 2 + 30x + 5y 2 + 30y + 90 = x 2 + 4xy + 4y 2 − 2x − 4y + 1 ⇐⇒ P : 4x 2 − 4xy + y 2 + 32x + 34y + 89 = 0 ,

L: x+2y=1
Y
−2
O
X
V
−1
(−2, −1)
P
F (−3, −3)
P
:−2x+y=3

P : 4x 2 4xy + y 2 + 32x + 34y + 89 = 0

P P ∈ P

P

P

 r : y o x − 2x o y x = x o + mt y = y o + nt , t ∈ R ,

=

:

y 2

= 4px

x

o

p

= 0

P = (x o , y o ) ∈ P

r : x = 0 x o = 0

y o x o

= 0

r :

P

P

= (x o , y o )

r

OX n

= 0

r ∩ P P
(y o + nt) 2 = 4p(x o + mt)
2
⇐⇒
n 2 t 2
+ 2y o nt + y
= 4px o + 4pmt
o
2
⇐⇒
n 2 t 2 + (2y o n − 4pm)t + (y
− 4px o ) = 0
o
⇐⇒
n 2 t 2
+ (2y o n − 4pm)t = 0
⇐⇒
t [n 2 t + (2y o n − 4pm)] =
0 ,
t = 0 P = (x o , y o )
2y o n − 4pm = 0 (m, n) ⊥ (2p, −y o )
2
x o = 0 y o = 0 y
=
4px o
o
(m, n) ⊥ (2p, 0) r
OX
r : x = 0
2
y
o
x o
= 0 y o
= 0 2p =
2x o
2
y
o
(m, n) ⊥
,
−y o (m, n) ⊥ (y o , −2x o )
2x
o
P = (x o , y o ) ∈ r
r
: y o x − 2x o y = −x o y o .
L
Y

P P

r

η P

P P

s F P r η s η

s
η
P
r
P
V
F
X

P : y 2 = 4px

P : y 2 = 4px p > 0

−−→ PF

s (1, 0) r n = (y o , 2x o ) η P P = (x o , y o )

F

= (p, 0)

P

= (p x o , y o )

B = 0 AC = 0

θ 1

−−→ PF

n

θ 2

n

(1, 0)

cos θ 1 =

x o y o + py o

y

2

o

+ 4x o (p x o ) 2 + y

2

2

o

cos θ 2 =

x o + p > 0